Environmental Problem-Solving: Balancing Science and Politics Using Consensus Building Tools : Guided Readings and Assignments from MITs Training Program for Environmental Professionals /: Guided Readings and Assignments from MITs Training Program for Environmental Professionals. (2020) - Susskind, Lawrence; Verdini, Bruno; Gordon, Jessica; Zaerpoor, Yasmin
No abstract available